Does the appointment of secretariesgeneral to lead global bureaucracies correlate with international power sharing? A longitudinal assessment based on empirical evidence from 1945 to 2016 - Valente,Mario Schettino (2019)
Abstract This paper focuses on secretaries-general, given their relative centrality in international politics, as they embody the power to explore institutional and personal agendas, and enjoy the chance to seek prestige for a country or region. Through descriptive statistics, this article analyzes the distribution of secretaries-general per country, reaching some noteworthy findings, especially regarding sharp changes in recent years.